A Juvenile Female with Ductal Carcinoma In situ Arising from a Fibroadenoma - Wan-Yu Hung; Chih-Ling Lee; Chin-Yao Lin (Journal of Cancer Research and Practice)
Ductal carcinoma in situ (DCIS) and atypical ductal hyperplasia are rare in teenagers. We report an incidental finding of DCIS in a 17-year-old girl who presented with a mass in the right breast. The pathology confirmed lower-grade DCIS in a fibroadenoma. She subsequently underwent right-breast conservative surgery (BCS) without radiotherapy or adjuvant hormone therapy. Six months of clinical surveillance was recommended, and she remained disease-free 25 months after BCS. Hormone therapy and radiotherapy are still controversial in juvenile patients with DCIS, and long-term surveillance and evaluation are still indispensable.